The neoliberal borderscape: Neoliberalism's effects on the social worlds of migrants along the Thai-Myanmar border - Loong, S (Elsevier, 2019)
This paper discusses neoliberalism's effects on migrants in Mae Sot, a town on the Thai-Myanmar border inhabited by approximately 200,000 migrants from Myanmar. Most literature on neoliberalism and borders focuses on how borders filter between “desired” and “unwanted” mobilities in the interests of capital accumulation. This paper takes a different approach; it argues that neoliberalism reconfigures the day-to-day social realities of migrants, who are embedded in families, communities, and a larger social system along the Thai-Myanmar border. During the 1980s, when a war economy thrived along the Thai-Myanmar border, migrants in Mae Sot established a semi-legal social system comprising schools, clinics, and community organisations, that allowed migrants to access functions ordinarily provided by a state. However, Myanmar's transition to a nominally civilian government in 2010 resulted in two changes on the border. Firstly, the Thai state is implementing projects to connect Mae Sot to transcontinental transport networks. Secondly, Western donors that funded community organisations in Mae Sot began re-routing their resources to supporting in-country programmes in Myanmar. Neoliberalism is the driving force for both these phenomena. Using the concepts of bordering and borderscapes, this paper discusses their combined effects on migrant children, families, and communities. Migrant children are increasingly denied opportunities to go to school, even as their parents become more deeply integrated into the border economy. Leaders of community organisations decrease their reliance on Western donors, but increase the burdens they place on other community members. The case of the Thai-Myanmar border demonstrates that a comprehensive understanding of neoliberalism's relationship with interstate borders must consider the ways in which socio-spatial identities are produced in dynamic relation with top-down efforts to regulate interstate boundaries. Concepts of bordering and the borderscape are central to this endeavor.